2011
DOI: 10.1002/acr.20481
|View full text |Cite
|
Sign up to set email alerts
|

RAPID3 (Routine Assessment of Patient Index Data 3) severity categories and response criteria: Similar results to DAS28 (Disease Activity Score) and CDAI (Clinical Disease Activity Index) in the RAPID 1 (Rheumatoid Arthritis Prevention of Structural Damage) clinical trial of certolizumab pegol

Abstract: Results. All measures were correlated significantly: RAPID3 with DAS28 and CDAI (rho > 0.7), higher than erythrocyte sedimentation rate with C-reactive protein level (rho ‫؍‬ 0.47). At 52 weeks, DAS28, CDAI, and RAPID3 low activity/ remission was seen in 30%, 44%, and 42% of CZP-treated patients versus 3%, 7%, and 10% of control patients. Good, moderate, and poor EULAR-DAS28 responses were seen in 30%, 51%, and 19% of CZP-treated patients versus 3%, 28%, and 70% of control patients, and for RAPID3 in 39%, 30%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 13 publications
2
56
0
Order By: Relevance
“…In addition, the results of this study suggest that clinicians should consider evaluating PROs in patients who report disease activity despite objective improvements, or introducing PRO‐based assessments, such as the Routine Assessment of Patient Index Data 3, which includes patient‐reported physical function, pain, and global assessment 30 into routine clinical practice. Particular attention should be paid to self‐reported pain, as pain appears to play a key role in patient perceptions of overall well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of this study suggest that clinicians should consider evaluating PROs in patients who report disease activity despite objective improvements, or introducing PRO‐based assessments, such as the Routine Assessment of Patient Index Data 3, which includes patient‐reported physical function, pain, and global assessment 30 into routine clinical practice. Particular attention should be paid to self‐reported pain, as pain appears to play a key role in patient perceptions of overall well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…65 Within the pilot trial the mean baseline RAPID3 score was just over 12 units (50% classified as high severity), with a SD of ≈ 5 units. At 7 months, the SDs were ≈ 6 units and 6.8 units for the advice and physiotherapy group and within the advice-only group, respectively.…”
Section: Stage 3: Physiotherapy For Hypermobility Trial -Quantitativementioning
confidence: 99%
“…Response criteria for the RAPID3 score have been proposed as a decrease in score of 3.6 units or more for a 'good' response, and 1.8 units or more for a 'moderate' response. 65 In terms of high, moderate and low severity, …”
Section: Routine Assessment Of Patient Index Data 3 Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the "artisan" approach is criticized for the following reasons: 1. The tool to evaluate the level of disease activity is not uniformly recognized (e.g., the DAS28-ESR 1 , the RAPID-3 14 , no swollen joints at ultrasonography 15 ). For example, in the study reported in this issue of The Journal 1 , the authors have noticed that the increase in treatments was not only based on the number of swollen joints but also the size of the joints affected by synovitis (larger joint involvement was more likely to influence treatment than number of swollen joints).…”
mentioning
confidence: 99%